THE ROLE OF PRIMARY GLOBAL PUBLIC GOODS IN INFORMATION SOCIETY - L. N. Shcerbakova (Vestnik MGIMO-Universiteta)
The article reflects the author's position as to the role of global public blessings in the period of transition to new models of development. The present stage of development of a society is considered as transitive. The maintenance of this transition is a formation of the information society. The information society leans against a new basis: the new base resources, new structure of a society, global character of the functioning, new collective reason. Expansion of a circle of the global public blessings can become one of possible ways of formation of the given society. In their structure articles of prime necessity at global level are allocated. We have carried the ecological blessings to them; the creative blessings; equality; the first material benefits – habitation, transport, a food and clothes. The nature of the global public blessings in modern conditions is characterized much more deeply, rather than principles of public using. Deep fundamentals of blessings of the given level are defined. Following lines are carried to them: first place in comparison with market interests of the countries; their dominating role in formation of new model of development of world economy; definition of their essence on formation stages, instead of distributions. Their manufacture should be planned by the world regulating centre. The role of global public blessings as tools of development and growth of new economy is defined. Radical difference of character of public blessings in the present system and global public blessings in the transitive society is revealed. Object of research is the modern stage of development. Targets of research are the global public blessings. Novelty of the article is caused by the author's scientific vision of the role of global public blessings in the formation of the new information society as defined.